The Philosophy of Selling Community: Developer Narratives and Resident Experiences of Privacy and Community in Gated Communities in Cairo - Raghib, Yosr Samir (AUC Knowledge Fountain, 2026)
Gated communities have become a global urban form with diverse impacts on their inhabitants. In recent years, Cairo has been expanding to the edges, and land that has always been a desert is now rapidly transforming into new cities that people are leaving their homes in the center of the city to move to seeking seclusion, security, privacy, and sense of community. Despite the tension proven between privacy and community, developers attempted to sell both concepts to coexist in gated communities in different manners to express their unique brand. Both concepts are defined differently by each developer, resulting in different approaches in their marketing strategies and design implementations. Therefore, this research attempts to study the nuanced applications of developers and ways that they express the two concepts and study how residents perceive these spatial configuration and elements. This leads to the overarching questions of this study “How do developers in Cairo's gated communities market and design for privacy and community to coexist, and how are these strategies perceived and experienced by residents?” with the underlying hypothesis being by marketing privacy and community, developers set the physical stage, but residents’ adaptations show that placemaking emerges through negotiation rather than fixed design. A comparative analysis is done to the design guideline keywords and their design applications used by four of the top developers in Cairo. This analysis allowed a nuanced lens for understanding the implementation of the two most important parameters sold in gated communities. Residential evaluation of the application tools is further studied through their feedback in surveys and interviews. The analysis of marketing narratives, spatial layouts, and resident feedback revealed two central themes: control and ownership. While developers employ tools such as gates, green buffers, and fences to market privacy and community, residents reinterpret these features in ways that often blur boundaries between inclusion and exclusion. This highlights that placemaking in gated communities is not predetermined by design but negotiated through everyday practices. The findings suggest that developers should integrate flexibility and feedback loops into design and management processes, ensuring closer alignment between promises and lived experiences. Future research can build on this by examining how resident practices and external forces reshape the meaning and use of these privatized spaces.